Retour au sport après plastie du ligament croisé antérieur: critères utilisés dans les clubs professionnels de football - Delvaux, F.; Rochcongar, P.; Bruyère, O.; Daniel, C.; Reginster, J.-Y.; Croisier, J.-L. (Science & Sports, 2015)
Purpose: To analyze how sport physicians decide, in their daily practice, when a professional soccer player with a reconstructed anterior cruciate ligament is able to get back to competitive activities. Materials and methods: Thirty-seven physicians for professional French and Belgian soccer teams filled in a specific questionnaire dedicated to: (1) return-to-play criteria after anterior cruciate reconstruction; (2) the importance they assigned to each of these criteria in the return-to-play decision; (3) the potential role of professionals, such as physiotherapists or physical coaches in this decision. Results: More than 80% of the respondents declared to use at least eight criteria in order to assess the player's ability to return to competitive soccer after anterior cruciate ligament reconstruction. The most important ones were (in order of importance): dynamic knee stability during a specific soccer exercise, muscle strength performance and normalization of knee flexion and extension ranges of motion. For most of these criteria (notably muscle strength), there was a lack of consensus about the choice of assessment parameters and the limit values allowing physicians to authorize or forbid the return-to-competition. A large majority of participants stated to take into consideration advices from physiotherapists or physical coaches for the return-to-play decision. Conclusion: Sport physicians of professional soccer teams use relevant criteria to assess players` ability to return to full sport after anterior cruciate ligament reconstruction. Further studies are required to determine the choice of assessment parameters and the limit values to assist physicians in return-to-play decisions.